Skills-Based Curriculum is an Innovative Way to Respond to the Demands of Globalization - Darmawan, Ari Wawan; Wijayanti, Anti; Ratnaningsih, Nani (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Skills-based Curriculum is an educational approach that focuses on developing students' practical abilities and soft skills, which are highly relevant in the era of globalization and the Industrial Revolution 4.0. By emphasizing applicative skills such as critical thinking, creativity, collaboration and communication, this Curriculum aims to prepare students for the challenges of the world of work and everyday life. This study aims to explore the benefits, challenges and strategic steps in implementing a skills-based curriculum. The study also highlights best practices at SMAN 10 Tasikmalaya that successfully integrate vocational programs in the skills-based Curriculum, such as cosmetology, automotive, and online business classes. This research uses a literacy study method that involves collecting, analyzing and synthesizing data from various sources, such as scientific journals, policy reports, books and related articles. Through this method, researchers were able to gain a deeper understanding of the theories, concepts and practices that have been applied in various educational contexts. The research also compared the implementation of skills-based Curricula in various schools, including SMAN 10 Tasikmalaya, to identify the supporting and inhibiting factors. The results show that although this Curriculum improves students' work readiness, challenges such as limited infrastructure, teacher readiness and evaluation systems still need to be overcome. Therefore, cooperation between the government, schools and industry is needed to ensure the successful implementation of the skills-based Curriculum.